The presence of Pentecostalism in the Evangelical Lutheran Church in Southern Africa - James K. Mashabela (African Journal of Pentecostal Studies)
Background: Pentecostalism in the Evangelical Lutheran Church in Southern Africa (ELCSA) is profoundly believed, strong and alive. In ELCSA, the Holy Spirit is affirmed and gives power to believers as the gracious gift that sustains and enables the very church to perform its duties of worshipping God, healing, preaching and meeting other spiritual needs. The Holy Spirit is actively acknowledged and worshipped as a gracious Spirit.